Targeting the AMP-Activated Protein Kinase for Cancer Prevention and Therapy - Kim, InYoung; He, Yu-Ying (Frontiers in Oncology, 2013)
Despite the advances in biomedical research and clinical applications, cancer remains a leading cause of death worldwide. Given the limitations of conventional chemotherapeutics, including serious toxicities and reduced quality of life for patients, the development of safe and efficacious alternatives with known mechanism of action is much needed. Prevention of cancer through dietary intervention may hold promise and has been investigated extensively in the recent years. AMP-activated protein kinase (AMPK) is an energy sensor that plays a key role in the regulation of protein and lipid metabolism in response to changes in fuel availability. When activated, AMPK promotes energy-producing catabolic pathways while inhibiting anabolic pathways, such as cell growth and proliferation—thereby antagonizing carcinogenesis. Other anti-cancer effects of AMPK may include promoting autophagy and DNA repair upon UVB damage. In the last decade, interest in AMPK has grown extensively as it emerged as an attractive target molecule for cancer prevention and treatment. Among the latest developments is the activation of AMPK by naturally-occurring dietary constituents and plant products—termed phytochemicals. Owing to their efficacy and safety, phytochemicals are considered as an alternative to the conventional harmful chemotherapy. The rising popularity of using phytochemicals for cancer prevention and therapy is supported by a substantial progress in identifying the molecular pathways involved, including AMPK. In this article, we review the recent progress in this budding field that suggests AMPK as a new molecular target in the prevention and treatment of cancer by phytochemicals.